The Process of Translating a Linear Program Problem into A Mathematical Representation - Nur Hasanah Syarief; Agustin Fatmawati (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
This research aims to describe the representation translation process in solving linear programming problems. The representation translation process will be explained at each stage of problem-solving according to Polya. The types of representation that will be explained are algebraic, numerical, graphic, and verbal. This research uses a descriptive qualitative approach. The research subjects consisted of two mathematics education students taking linear programming courses. Both subjects are students with high mathematical abilities who have good communication skills so that researchers can explore more in-depth information about the representation translation process. The instrument in this research is a linear program test which consists of two problems. The research results showed that subject 1 (S1) and subject 2 (S2) fulfilled three stages of problem-solving, namely understanding the problem, making a plan, and implementing the plan. Both subjects used all four representations in solving problems. The translation process that occurs starts with exploring sources, compiling initial knowledge, building targets, and determining suitability.